Decision Support Project BP-2: Spatial and Economic Analysis for Policy and Decision Support in Agriculture and Environment: Summary, Annual Report 2006 - International Center for Tropical Agriculture (2007)
Our goal is to improve the targeting of investments in agricultural and NRM research and development through economic and geographic analysis. Our objective is to develop and provide analysis, information and tools to improve decisions about where, when and how innovations can be implemented to enhance rural livelihoods in a sustainable and equitable manner.